Tratamento de efluente kraft por bioaumentação com bactéria autoctone imobilizada em meio suporte esponjoso - Coelho, Bruna Durat (2023)
Brazil is considered a world reference in paper production, a sector that contributes with estimates of 46.5% of the national gross domestic product. Extensive production, which entails the exhaustive use of water, raw materials, energy and chemicals, consequently originating effluents historically identified as polluted, due to the presence of high concentrations of organic matter and recalcitrant compounds that induce color and ecotoxicity to it, configuring it as a concern for health and the environment. Strategies for the treatment of wastewater from the paper industry have been studied, such as bioaugmentation with bacteria, due to the potential metabolism adapted to these adverse environmental conditions. When used in conjunction with immobilization techniques, providing that the inoculum of native bacteria, called autochthonous, develops in the form of biofilms on the surface of a support medium that provides greater surfaces for adhesion and growth of the bacterial population. Thus, the objective of this work was to evaluate the treatment of kraft pulp effluent by bioaugmentation with the autochthonous bacteria Advenella kashmirensis. The treatment of effluent from the kraft pulp industry was carried out using aerated lagoons on a bench scale. The research was divided into phase I, in which the treatment of the effluent was investigated from the addition of support medium units of the aquaporousgel (APG) type without the presence of immobilized bacteria. Phase II, in which the performance of the biofilm of the autochthonous bacteria immobilized on the APG support medium is evaluated. Phase III, where the treatment potential of A. kashmirensis was evaluated in the form of planktonic life applied directly to the effluent of the lagoon. The performance of the inoculum and the APG medium was evaluated by the parameters removal of biochemical oxygen demand (BOD5), chemical oxygen demand (COD), total organic carbon (TOC), color, total phenolic compounds (CFT), ligninic compounds (CL) and spectral area. The treatments carried out in the presence of the free support medium (phase I) or containing the immobilized preparations (phase II), were efficient in the treatment of the physical-chemical parameters analyzed. Also highlighting that the presence of immobilized bacteria had a higher removal for CFT and CL, also observed by the analysis of the spectral area, with removal of approximately 30% of UV-Vis absorbing compounds contained in the effluent. Phases II and III, in which the bacteria were inoculum, showed the potential to remove recalcitrant compounds, removing 8% of the effluent color. Associated with these results, electronic micrographs of the APG sponges used in the immobilization test and others added to the pond in phase I and II of the research were observed. The images made it possible to investigate the growth of the biofilm, confirming adherence to the interior matrix of the APG. Thus, it was possible to immobilize the autochthonous bacteria A. kashimirensis in the spongy support medium and this product was effective in the treatment of kraft cellulose effluent, achieving higher contaminant removals than those in the absence of the bacteria.